Upaya Peningkatan Pendapatan Keluarga Melalui Usaha “ Bandeng Presto” - - Sulistyowati; Totok Sumaryanto; Danang Dwi Saputro; - Sunyoto (Patria : Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of IbW activities is to solve problems faced by the community (KUB Putri Tirang) whose efforts are not carried out continuously. Implementation Method: 1) Through the process of counseling, training and mentoring at the house of the chairman of the bandeng Group Presto "Putri Tirang" RT 07 RW 03 Tapak village with a pot of Presto with a capacity of 20 kg, the pilot was assisted by instructors. Materials provided: Introduction of materials, tools and pots presto capacity of 20 kg. Strategies: Utilizing the chairman of the group "Putri Tirang", members of the interested group, for training in the development of entrepreneurship making bandeng Presto. Outside activities are expected: The trainees can independently develop the entrepreneurship of making Presto milkfish and meet the needs of Presto bandeng in Semarang City. Knowing the level of profit, return on investment, and break-even point is carried out business analysis. From the calculation, it turns out that the business of making bandeng Presto Household Scale is financially profitable, with a price of Rp 4,868.53, - per head, BEP production of 12 kg (72 heads) per production. Presto's bandeng business "Putri Tirang" resulted from economically profitable innovations so that it needs to be imitated by its members and carried out continuously.